2010
DOI: 10.1590/s0100-83582010000300008
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness of alexandergrass or Bengal dayflower with soybean

Abstract: Weeds compete with field crops mainly for water, light and nutrients, and the degree of competition is affected by the weed density and the intrinsic competitive ability of each plant species in coexistence. The objective of this research was to compare the competitiveness of alexandergrass (Brachiaria plantaginea) or Bengal dayflower (Commelina benghalensis) in coexistence with soybean, cv. M-Soy 8045. A factorial experiment (2 x 5) with two weed species and five competition proportions was carried out in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 26 publications
0
14
0
6
Order By: Relevance
“…Research using replacement series studies has shown that soybean crop has competitive advantage in relation to weeds, grasses and broadleaves (Bianchi et al 2006;Dias et al 2010;Moraes et al 2009;Wandscheer and Rizzardi 2013). However, the results for barnyardgrass have shown that this weed usually has competitive advantage in relation to irrigated rice cultivars Aminpanah et al 2012;Gealy et al 2005), and this response is attributed to the high morphophysiological similarity between the species.…”
Section: Introductionmentioning
confidence: 99%
“…Research using replacement series studies has shown that soybean crop has competitive advantage in relation to weeds, grasses and broadleaves (Bianchi et al 2006;Dias et al 2010;Moraes et al 2009;Wandscheer and Rizzardi 2013). However, the results for barnyardgrass have shown that this weed usually has competitive advantage in relation to irrigated rice cultivars Aminpanah et al 2012;Gealy et al 2005), and this response is attributed to the high morphophysiological similarity between the species.…”
Section: Introductionmentioning
confidence: 99%
“…Já o capimmarmelada (Brachiaria plantaginea) é uma planta daninha muito frequente em culturas anuais e perenes no Brasil, sendo muito competitiva quando presente em culturas anuais (Brighenti & Oliveira, 2011), como soja e milho, provocando prejuízos consideráveis ao rendimento e à qualidade da produção (Dias et al, 2010;Pereira et al, 2010).…”
Section: Introductionunclassified
“…A infestação de plantas daninhas durante o desenvolvimento inicial da cultura da soja representa importante problema para as lavouras agrícolas, pois resulta em perdas signifi cativas no rendimento de grãos, dependendo da composição específi ca da comunidade infestante e da habilidade competitiva das espécies em convivência (DIAS et al, 2010). LAMEGO et al (2005) destacam que a soja é uma espécie que apresenta elevada plasticidade e mostra respostas adaptativas às condições de ambiente e manejo ao qual é submetida.…”
Section: Resultsunclassified
“…Em análise à resposta da soja com a interferência do capim-pé-de-galinha, constatouse que as variáveis matéria seca da parte aérea, raiz e total não diferiram dos valores obtidos nos monocultivos (Tabela 3). O contrário foi observado por CARVALHO et al (2011), quando o capimmarmelada foi mais sensível que a cultura do trigo em relação à competição intraespecífi ca. Também, AMINPANAH et al (2012) constataram que o arroz (cultivar 'Hashemi') apresentou melhor peso da matéria seca da parte aérea quando conviveu com plantas da mesma espécie.…”
Section: Resultsunclassified